(untitled) (Journal of Education and Development, 2020)
The idea of student-centered learning and education has been sweeping through teaching pedagogy for a number of years, with a heavy emphasis in the realm of ESL/EFL. Students have been given the ability to choose topics, and overall classroom atmosphere in the goal of increased student engagement and participation. However, the specific activities students would prefer to engage in have not been researched extensively. The present study examined the learning activity preferences of college students majoring in languages and non-languages in a college EFL classroom in Korea. Students were given a survey which assessed three different parts: their perceived English abilities, their preferences in teacher quality and classroom, and their preferences in activities. The data obtained indicated that students prefer a class which incorporates free-talking as an activity and as an overall methodology. These findings allow teachers to focus specifically on what students would like to practice in a classroom, but also leave a large gap for teachers to fill in terms of how to implement said quality into an entire curriculum.